Palladium‐Catalyzed Silver‐Mediated α‐Arylation of Acetic Acid: A New Approach for the α‐Arylation of Carbonyl Compounds. Issue 6 (24th April 2014) - Wu, Guo‐Jie; Guan, Jing; Han, Fu‐She; Zhao, Yu‐Long
Abstract A new approach for the α‐arylation of acetic acid through Pd‐catalyzed silver‐mediated direct CH arylation of acetic acid with aryl iodides was developed. This protocol provided a straightforward method for the synthesis of a diverse set of α‐phenylacetic acids.